1986
DOI: 10.1007/bf02309589
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic effects of feeding a high protein/low carbohydrate diet as compared to a low protein/high carbohydrate diet to rainbow troutSalmo gairdneri

Abstract: Groups of trout were fed either a high protein/low carbohydrate (HP/LC) or a low protein/high carbohydrate (LP/HC) diet for 16 weeks. Fish fed the HP/LC diet had significantly higher levels of protein, ninhydrin positive material and tryptophan in plasma as well as lipid and protein in liver, but lower levels of glucose in plasma, glycogen in liver and a lower hepatosomatic index compared with fish fed the LP/HC diet. There were no differences concentrations of tryptophan or serotonin in the brain of fish fed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
1
4

Year Published

1992
1992
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(52 citation statements)
references
References 31 publications
4
43
1
4
Order By: Relevance
“…Conversely, intrinsic physiological limitations may impede the evolution of herbivory in lizards. In other vertebrate classes, carnivorous or insectivorous species are unable to down-regulate rates of endogenous protein catabolism when feeding on low-protein diets, often resulting in negative nitrogen balance (Green et al, 2008;Robbins, 1983;Rumsey, 1981;Walton, 1986), whereas herbivores generally have physiological adaptations that allow them to maintain nitrogen balance on low-protein foods Robbins, 1983). Thus, lizards might be limited in their ability to feed on lownitrogen foods and maintain nitrogen balance.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, intrinsic physiological limitations may impede the evolution of herbivory in lizards. In other vertebrate classes, carnivorous or insectivorous species are unable to down-regulate rates of endogenous protein catabolism when feeding on low-protein diets, often resulting in negative nitrogen balance (Green et al, 2008;Robbins, 1983;Rumsey, 1981;Walton, 1986), whereas herbivores generally have physiological adaptations that allow them to maintain nitrogen balance on low-protein foods Robbins, 1983). Thus, lizards might be limited in their ability to feed on lownitrogen foods and maintain nitrogen balance.…”
Section: Introductionmentioning
confidence: 99%
“…Walton (1986) reported that low carbohydrate and high protein food intake affected low activities of glycolytic enzymes and citric acid cycle in rainbow trout.…”
Section: Differences In Metabolic Parameters Between Wild and Hatchermentioning
confidence: 99%
“…Walton (1986) reported that low carbohydrate and high protein food intake induced low activities of glycolytic enzymes and the citric acid cycle in rainbow trout. Brauge et al (1994) demonstrated that elevated digestible carbohydrate intake resulted in glycaemia in rainbow trout.…”
Section: -3 Differences In Metabolism Between 1+ Wild and Hatchery mentioning
confidence: 99%